PROBLEMS OF THE QUALITY OF SCIENTIFIC PERIODICALS PUBLISHED IN HIGHER EDUCATION INSTITUTIONS IN LITHUANIA - Šakytė, Milda (Knygotyra, 2016)
The aim of the article is to identify the factors that determine the quality of scientific periodicals published in higher education institutions of Lithuania based on formal scientific evaluation criteria. In order to achieve this goal, the following objectives have been identified: analyzing the characteristics of scientific periodicals published in higher education institutions and conducting a study to identify the factors that determine the quality of scientific periodicals based on formal evaluation criteria for scientific periodicals. A quantitative study of Lithuanian higher education institutions scientific periodicals shows that most of the periodicals are published in PDF format and provide open access. A quarter of the scientific periodicals are valued in Web of Science and Scopus databases. It is important to note that the main problems for publishing such scientific periodicals are related to the websites of inadequate quality. The empirical study, based on interviews conducted with eleven Editors in Chief of the scientific periodicals, has disclosed that a publishing house has a fundamental role for the quality of scientific periodicals. The quality of scientific periodicals is influenced by a sufficient numbers of human resources, applicable managerial, technical and promotional solutions. Secondly, the research results reveal that, even though business-related decisions effect the quality of scientific periodicals, an approach to scientific periodicals publishing as a commercial activity is still unacceptable. In conclusion, it should be stated that the main goal of scientific periodicals of Lithuania, based on national and international science evaluation criteria, is to get included in Web of Science and Scopus databases. For this reason, the editors are looking for opportunities to improve the content of the journals as well as make the publications more visible online. Judging by the efforts made by the management and the current number of scientific periodicals in Lithuania, it can be assumed that the number of formally evaluated scientific journals will increase in the future.